Background independence in classical and quantum gravity - Read, J (2016)
Background independence is sometimes claimed to be the defining characteristic of general relativity (GR), and a necessary feature of any candidate quantum extension. In this thesis, we appraise numerous definitions of background independence, before assessing whether various spacetime theories—both classical and quantum—manifest this quality. Our aims are threefold: (i) to clarify the best possible understanding of background independence; (ii) to assess the extent to which, at the level of classical spacetime theories, background independence is characteristic of GR alone; and (iii) to assess whether this quality is in fact manifest in some of our best candidate quantum gravity theories.